A Cross-Country Perspective On Health Spending İn The OECD - Serpil Tomak (South Eastern European Journal of Public Health, 2025)
Objective: This study examines the determinants of health expenditures across 38 OECD countries with varying levels of development over the period 2000–2024. Methods: Descriptive statistics, including means, standard deviations, medians, and ranges, were used to summarize the research parameters. The Kolmogorov-Smirnov test, along with skewness and kurtosis values, was employed to assess the normality of data distribution. As the variables were expressed in ratio form, unit root tests were deemed unnecessary. Parametric analytical methods were applied. Pearson’s product-moment correlation was conducted to examine relationships between variables, and a linear regression model was utilized to assess the effects of independent variables. All analyses were performed using SPSS version 25.0 for Windows, with a 95% confidence interval. Results: Pearson correlation analysis showed that per capita health expenditure was strongly associated with several key variables, including the number of physicians (r=0.928), elderly population (r=0.993), and GDP (r=0.939), all at p<0.01. Interestingly, negative correlations were observed with alcohol (r=-0.962) and tobacco use (r=-0.972), suggesting that increased health spending may contribute to reducing harmful behaviors, possibly through targeted public health initiatives and prevention programs. Furthermore, regression analysis indicated that life expectancy, elderly population ratio, and GDP were significant predictors of health expenditure per capita (R²=0.996; p<0.01), whereas for health expenditure as a share of GDP, hospital bed density, alcohol use, life expectancy, elderly population, and GDP were influential (R²=0.967; p<0.01). The negative coefficients for life expectancy and alcohol/tobacco use suggest that both the preventive impact of health spending and premature mortality may contribute to variations in health expenditure patterns across countries. Conclusion: This study found that healthcare expenditures in OECD countries were driven by demographic, economic, and behavioral factors. Higher GDP and elderly population increased spending, while life expectancy and risky behaviors like alcohol and tobacco use showed inverse associations. The results highlight the need for investments in aging, prevention, and economic resilience.